Emigration and Diaspora Policies in the Age of Mobility - Weinar, Agnieszka (Springer International Publishing : Imprint: Springer, 2017)
This volume examines the ways different countries around the world have responded to rising numbers of mobile citizens. Complete with detailed case studies, it provides a groundbreaking and global analysis of emigration and diaspora policies in the 21st century. First, an introduction considers factors that determines a state's policy choices. It draws on rich empirical material to present readers with information on the determinants of policy definition and implementation, reactions to emigration, and converging and diverging trends. Next, the volume offers detailed case studies from 15 countries around the world, including Argentia, Vietnam, Senegal, the Russian Federation, Denmark, and Turkey. Coverage for each country critically analyzes its emigration or diaspora policies as well as how these policies affect its mobile citizens. The contributors also place the policies in context and explore the consequences of pertinent rules and provisions. In addition, a conclusion presents a comparative analysis of all case studies as well as details a set of best practices. Emigration and immigration are two sides of the same c oin that every country experiences and, in one way or the other, must face. This book offers readers a new look on diaspora and emigration governance across the globe and explores the future paradigm of reactions to emigration.
Keywords: Social sciences.; Political science.; Emigration and immigration.; elektronické knihy; electronic books